The investiture procedure in Spain: an analysis in light of the recent experience - López Rubio, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
More than three decades of a strong two-party system ended after the Spanish general elections of 2015 and 2016. Until then, investiture had never been particularly difficult and the formation of the government had taken place rapidly. The new political situation, that produced a 315-day span without government, suggests reviewing the constitutional rules for the election of the President of the Government and discussing whether or not some legal reforms are convenient.